PERUBAHAN GAYA HIDUP PESERTA DIDIK AKIBAT MEDIA SOSIAL DI SMA NEGERI 6 KOTA KUPANG - Lusia Ijung (Prosiding Ilmu Pendidikan dan Keguruan, 2023)
The aims of this study were (a) to find out the lifestyle of students in using social media (Tik-tok), (b) to find out the impact of Tik-Tok social media on the lifestyle of students. The method used in this study was this research using qualitative method, with a descriptive approach, data collection techniques were carried out through interviews, observation, and documentation with sociology students and teachers. The results of this study show the first few findings, the lifestyle of students in using social media Tik-Tok students get positive values ​​can recommend in terms of dressing for themselves so that they can be outfit stylists in a positive context. Meanwhile, the negative context of the lifestyle of other students only tends to use Tik-Tok social media both in class and outside of school, so that teaching and learning activity decreases and grades greatly decrease. Second, the impact of Tik-Tok social media on student behavior, there are more negative impacts, such as students learning less, playing cellphones more than opening books. Students also don't care about the community environment, get together to discuss unnatural things, especially students are more likely to find out what will be broadcast on social media rather than the time to study.